Христологічна антропологія і діалогічна філософія: історична експлікація та зіставлення вихідних підстав - Возняк, О. Т.; Voznyak, O. T. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті обґрунтовано ідею, що основні моменти, які відзначають православні мислителі, аналізуючи христологію, внутрішньо узгоджені з методологічними принципами діалогічної філософії, тому наявність співзвучностей визначена не впливами один на одного, а й тим, що дані концепції містять християнські корені. The article gives a background to the idea that the main moments which are essential to the orthodox philosophers in Christology, are concurrent with the dialogical philosophy’s methodological principles. Therefore some common features of those schools depends not on the influence of one conception on another but on the fact that both of them have Christian roots. The dogma of Chalcedon has all necessary means for dynamic and versatile exploring «The Other»-problem. The human being in the fullness of his entity can be extremely distinctly described in Chalcedon terms: we find «invariable, inseparable» presence of human and divine, natural-biological and spiritual, sensual and mental; we ought to distinct but not to divide. So taking a look at the authentic Christian dialogism possesses new heuristic potential.
The Christological Anthropology and the Dialogical Philosophy: Historic Explication and Comparison of the Basic Principles
Keywords: христологія; Christology; діалогізм; dialogism; зустріч; facing; утілення; embodiment; незлиянність; inmerging; нероздільність; inseparation